Perspective Leader - Follower: Situational Theory of Leadership - Marić, Slobodan; Rodić, Marijana; Strugar Jelača, Maja; Bjekić, Radmila (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Traditional theories of leadership are limited in themselves by the possibility of exploring influences on the leader-follower relationship. This perspective changes completely with situational models of leadership. Based on Situational Leadership Theory (SLT) such as the Hersey and Blanchard leadership model, the optimal leadership style depends on a number of factors and situations. Within this theory, a leader behavior is determined by situational factors including psychological maturity, general motivational attitudes of followers, and professional maturity. In the examination of the mentioned factors, research was conducted on a sample that has the characteristics of a random sample of the final basic set, where a sample plan with repetition and a known sampling probability is present. A sample of size n = 100, with a size of 0.10, was formed on the basis of the list of 100 largest companies in the Republic of Serbia in 2019. The research used situational leadership measures developed by Hersey and Blanchard in the form of the LEAD Other Scale and Readiness Scale - Staff Member Rating Scale to achieve the objectives of the research in determining the differences between (in) matching leadership style and employee maturity from the aspect of LeadScore. The results of the research fully confirm the Hersey and Blanchard Situational Theory of Leadership.